2022
DOI: 10.1002/jor.25488
|View full text |Cite
|
Sign up to set email alerts
|

From replantation to transplantation: The evolution of orthoplastic extremity reconstruction

Abstract: For more than six decades, the use of the operating microscope for extremity surgery has led to remarkable advances in the management of orthopedic trauma, tumors, infections, and congenital differences. The microsurgical reconstructive ladder ascends from basic microsurgical procedures such as a digital artery or nerve repair to more complex procedures such as autologous tissue transplantation. Functional muscle transfers, toe-to-hand transfers, and recently vascularized composite allotransplantation are the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 96 publications
0
5
0
Order By: Relevance
“…Traumatic major limb mutilation is one of the main causes of limb loss. Even though replantation of limb mutilation is increasing gradually with the development of microsurgery and surgical techniques [ 1 , 4 , 27 ], postoperative wound infection can result in multiple operations and even delayed amputation, which may increase the financial and psychological burden of patients [ 2 , 4 , 16 ]. This study found that postoperative wound infection was common in patients with severe traumatic major limb mutilation, and most of the pathogenic bacteria were multi-drug resistant bacteria, which was associated with ischemic time, degrees of wound contamination, stress hyperglycemia, and MESS.…”
Section: Discussionmentioning
confidence: 99%
“…Traumatic major limb mutilation is one of the main causes of limb loss. Even though replantation of limb mutilation is increasing gradually with the development of microsurgery and surgical techniques [ 1 , 4 , 27 ], postoperative wound infection can result in multiple operations and even delayed amputation, which may increase the financial and psychological burden of patients [ 2 , 4 , 16 ]. This study found that postoperative wound infection was common in patients with severe traumatic major limb mutilation, and most of the pathogenic bacteria were multi-drug resistant bacteria, which was associated with ischemic time, degrees of wound contamination, stress hyperglycemia, and MESS.…”
Section: Discussionmentioning
confidence: 99%
“…The earlier the repair, the better the effect. Godina's practice of early repair and combined repair pioneered the concept of orthoplastic surgery 41 . Boriani 42 conducted a prospective multi‐center cohort study which include a total of 160 patients.…”
Section: Discussionmentioning
confidence: 99%
“…Godina's practice of early repair and combined repair pioneered the concept of orthoplastic surgery. 41 Boriani 42 conducted a prospective multi-center cohort study which include a total of 160 patients. Of these, 70% were treated with an orthoplastic approach, whereas 30% were treated by an orthopaedic team.…”
Section: Effect Of the Time From Injury To Flap Coverage On Prognosismentioning
confidence: 99%
“…Over the past six decades, the field of microsurgery has undergone a significant evolution, beginning with the revascularization and replantation techniques and then extending to the utilization of free microsurgical transfer for the remediation of tissue defects and the implementation of composite tissue transfer methods. A notable development is the concept of chimeric flaps and the application of functional muscle transfers to address motor deficits following brachial plexus injuries or Volkman’s ischemic contracture, progressing further to the realm of hand transplantation [ 12 , 102 ].…”
Section: Overview Of Reconstructive Paradigmsmentioning
confidence: 99%
“…This currently occupies the highest level on the microsurgical reconstructive ladder and will likely continue to do so with the advent of technological and immunological modern strategies. Figure 4 presents the microsurgical reconstructive ladder including all these new therapeutic strategies [ 12 , 102 , 108 , 113 , 114 , 115 , 116 ].…”
Section: Overview Of Reconstructive Paradigmsmentioning
confidence: 99%